Strategic approach to sustainable business of Galenika Fitofarmacija A.D. in a context of accession of Republic of Serbia - Zecevic , Dijana (Applied Studies in Agribusiness and Commerce, 2009)
Strategic management is ultimately concerned with the quest for sustainable advantage. To be practical, advantage for commercial firms concerns earnings and sustainable means a concern with earnings into the future. Pearce and Robinson define strategic management as a set of decisions and actions that results in the formulation and implementation of plans designed to achieve a company’s objectives. David says that strategic management can be defined as the art and science of formulating, implementing, and evaluating cross-functional decisions that enable an organization to achieve its objectives. Strategy is also hierarchical concept – it takes place at three different levels: corporate, business, and functional. These levels correspond with the activities of managers in different parts of the organization.